A Correction Method for the Underwater Shock Signals of Floating Shock Platforms Based on a Combination of FFT and Low-Frequency Oscillator - Peng Wang; Ming Yan; Lei Zhang; Mingyuan Zhang (Shock and Vibration)
Accurate shock loading is required for evaluating and analyzing the shock resistance of warship equipment. However, measured shock acceleration signals contain trend term errors, which cause serious low-frequency distortion of the shock response spectrum (SRS). We propose a combination method of fast Fourier transform (FFT) and low-frequency oscillator for correcting the underwater shock signals. Based on the equal displacement line fitted by the measured displacement response data, the Fourier transform spectrum of the shock acceleration signal is corrected for eliminating low-frequency errors. The results of underwater explosion tests on a floating platform indicate that the average difference between the equal displacement line and SRS in the low-frequency band (4∼20 Hz) can be reduced from 14.7% to 3.5%, and the mid-high-frequency band without the trend term is nearly unaffected. The corrected SRS can faithfully reflect the actual shock environment of the warship equipment at a specific installation location of the floating shock platform.